A Literature-Derived Pedagogical Framework for Augmented Reality-Supported Deeper English Learning in Junior High Schools: An Integrative Review - Suardi; Sahrir; Alviani; Intan Ramadhani; Riska (Universitas Islam Negeri Palopo, 2026)
Augmented reality (AR) can support engagement, visualization, multimodal literacy, vocabulary learning, and academic achievement, but its value depends on pedagogical design, teacher readiness, usability, and assessment. This integrative review synthesized 20 peer-reviewed journal articles published between 2019 and 2025 to formulate a pedagogical framework for AR-supported deeper English learning in junior high schools. A structured extraction matrix and thematic synthesis were used to examine AR affordances, instructional design, language outcomes, teacher competence, user experience, and school context. Five themes emerged: AR as cognitive and multimodal scaffolding; pedagogical sequencing as a condition for effectiveness; operationalization of deeper learning; teacher readiness and TPACK; and classroom feasibility. The proposed framework integrates AR across understanding, applying, and reflecting. Within understanding, AR supports essential understanding, applied understanding, and values-and-character understanding by connecting language with visual, spatial, cultural, and contextual representations. Applying requires contextual language use and authentic products, while reflecting requires evaluation of strategies, performance, meaning, and values. The framework also specifies teacher, learner, and media roles, assessment evidence, implementation fidelity, and user acceptance. AR should therefore be treated as an integrated cognitive-pedagogical tool rather than an isolated digital medium.